2021
DOI: 10.4103/jmp.jmp_81_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phase-gated and amplitude-gated dose delivery to a moving target using gafchromic EBT3 film

Abstract: IntroductIonLung stereotactic body radiation therapy (SBRT) is used for the treatment of early-stage nonsmall cell lung cancer and metastatic lung tumors. [1,2] SBRT treatments are delivered in a hypofractionation mode, with high doses in a few fractions (from 3 to 8 fractions), depending on tumor localization (central or peripheral tumors). [3] The treatment of lung cancer with high doses can be impacted by tumor motion and proximity to the organ at risk. [4][5][6][7] Various techniques were developed to ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The prosthetic tumor is 3D printed using PLA material. Its outer section is a spherical object with a diameter of 3 cm, whereas its internal section is semihollow with a diameter of 2 cm to facilitate the placement of a Gafchromic film (EBT3), which is to inspect radiation doses and accuracy (Savanović et al 2021), as shown in figure 3(a). The example of beam delivery is in figure figure 3(b).…”
Section: Tumormentioning
confidence: 99%
“…The prosthetic tumor is 3D printed using PLA material. Its outer section is a spherical object with a diameter of 3 cm, whereas its internal section is semihollow with a diameter of 2 cm to facilitate the placement of a Gafchromic film (EBT3), which is to inspect radiation doses and accuracy (Savanović et al 2021), as shown in figure 3(a). The example of beam delivery is in figure figure 3(b).…”
Section: Tumormentioning
confidence: 99%